Long-Term Efficacy and Safety of Asenapine or Olanzapine in Patients with Schizophrenia or Schizoaffective Disorder: An Extension Study - Schoemaker, J.; Stet, L.; Vrijland, P.; Naber, D.; Panagides, J.; Emsley, R. (Pharmacopsychiatry, 2012)
Safety and efficacy results, collected in schizophrenia and schizoaffective disorder patients treated for up to nearly 3 years, are presented for asenapine and olanzapine.Patients completing a 52-week randomized double-blind core study on flexible-dose asenapine (5 or 10 mg BID) or olanzapine (10 or 20 mg QD) could continue treatment until study blind was broken.290 patients on asenapine and 150 on olanzapine continued treatment for variable lengths of time [mean±SD (range) 311.0±146.1 (10 − 653) d and 327.4±139.6 (15 − 631) d, respectively]. Adverse event (AE) incidence was lower during the extension (asenapine, 62%; olanzapine, 55%) than during the core study (78%, 80%). In both groups, body weight increase and incidence of extrapyramidal AEs were negligible during the extension. Mean PANSS total score changes during first year of treatment were  − 37.0 for asenapine and  − 35.3 for olanzapine, with further changes of 1.6 for asenapine and  − 0.8 for olanzapine at the extension study endpoint.Clinical stability on asenapine as well as olanzapine was maintained, with few recurrent or newly emerging AEs beyond 1 year of treatment.NCT number: NCT00212771
Keywords: asenapine; schizoaffective disorder; schizophrenia; tolerability; olanzapine